2016
DOI: 10.1080/03007995.2016.1222517
|View full text |Cite
|
Sign up to set email alerts
|

An abuse-deterrent, microsphere-in-capsule formulation of extended-release oxycodone: alternative modes of administration to facilitate pain management in patients with dysphagia

Abstract: Oxycodone DETERx is the first ER oxycodone formulation that can be administered either intact, sprinkled onto soft foods, or via NG/G tubes, thereby providing options for treating pain in patients who have difficulty swallowing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…The physicochemical properties of Xtampza ER that limit its ability to be manipulated may help reduce the incidence of unintentional misuse by patients or their caregivers who manipulate analgesics to make them easier to swallow or to enable a different route of administration. In addition to these abuse-deterrent properties, Xtampza ER can be administered via multiple modes [11], allowing clinicians to prescribe one analgesic that can provide treatment for patients who require different modes of administration (e.g., intact, sprinkled onto food, poured into a nasogastric/gastric tube).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physicochemical properties of Xtampza ER that limit its ability to be manipulated may help reduce the incidence of unintentional misuse by patients or their caregivers who manipulate analgesics to make them easier to swallow or to enable a different route of administration. In addition to these abuse-deterrent properties, Xtampza ER can be administered via multiple modes [11], allowing clinicians to prescribe one analgesic that can provide treatment for patients who require different modes of administration (e.g., intact, sprinkled onto food, poured into a nasogastric/gastric tube).…”
Section: Discussionmentioning
confidence: 99%
“…An added benefit of Xtampza ER is the microsphere-in-capsule design. Each microsphere functions as an individual ER drug delivery system, allowing for multiple modes of administration (intact, sprinkled onto food and via nasogastric/gastric tubes) without losing the ER characteristics [11]. This unique design may limit the misuse that occurs when patients, patient caregivers and healthcare providers manipulate ER abuse-deterrent formulation analgesics to facilitate swallowing or enable other modes of administration [11].…”
mentioning
confidence: 99%
“…Several studies (described in detail in this review) have demonstrated that this microsphere technology ensures the maintenance of the ER characteristics if the capsule contents are crushed or chewed and ingested orally or crushed and insufflated (snorted) intranasally; as a result, oxycodone DETERx is the first oral ER-formulated opioid without language in its boxed warning pertaining to crushing or chewing leading to potential exposure to a fatal dose of opioid. The oxycodone DETERx formulation allows for alternative modes of administration, including sprinkling directly into the mouth from a dosing cup or onto soft foods, as well as administering via nasogastric or gastrostomy tubes [21, 22], making oxycodone DETERx an option for patients with chronic pain who also have difficulty swallowing.
Fig. 1Photograph showing the spherical, microparticulate nature of oxycodone DETERx capsule contents.
…”
Section: Extended-release Oxycodone With Deterx Technology: a Microspmentioning
confidence: 99%
“…The mean plasma oxycodone concentrations over time were superimposable for sprinkled and intact oxycodone DETERx (Fig. 2a), and the peak serum concentration and extent of oxycodone absorption were bioequivalent (Table 2) [20, 22].
Fig.
…”
Section: Dosing Considerations and Optionsmentioning
confidence: 99%
See 1 more Smart Citation